Losses from top spoilage in horizontal silos - D.L. Holthaus; B.E. Brent; L. Pfaff; K.K. Bolsen; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1995)
The top 3 ft of silage from 127 horizontal silos was sampled at three locations across the width of the silo during a 4-year period (1990 through 1993). Ninety-six percent of the silages were either corn or forage sorghum, and only 18 percent of the silos were sealed with polyethylene sheeting . Losses of organic matter (OM) from spoilage were estimated by using ash content as an internal marker. Sealing silos dramatically reduced the estimated spoilage losses in the top 3 ft. All silages had greater estimated spoilage losses in the top 18 inches in 1991 and 1993 than 1990 and 1992. Sealing reduced spoilage losses of OM in the to p 18 inches by 16, 37, 19, and 36 percentage units in 1990 through 1993, respectively , and in the second 18 inches by 4, 13, 3, and 7 percentage units. Dry matter (DM) contents were lower for forage sorghum silages in the top 18 inches than for corn silages in the first 3 years, and i n all 4 years, DM contents for sealed silages were lower than those for unsealed silages. Silage had higher pH values in the top 1 8 inches than in the second 18 inches.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Survey; Top spoilage; Silage; Bunker; Trench